(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify (the effect of the strategy of climbing the plateau in acquiring geographical concepts among the first intermediate grade students).To achieve this, the researcher chose an experimental design with partial control of two experimental groups with a post-test, and the researcher intentionally chose a sample of first-grade intermediate students from Baghdad Intermediate School for Girls affiliated to the Directorate of Education, Baghdad / Al-Rusafa II for the academic year 2011/2012 AD, for the purpose of applying the experiment.